DETERMINASI KEPUASAN, KOMITMEN DAN KOMPETENSI TERHADAP KINERJA GURU DI SEKOLAH MENENGAH ATAS NEGERI 2 TEBING TINGGI KABUPATEN MERANTI - Aprilian Aprilian; Chablullah Wibisono (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2017)
This research discusses about the determination of satisfaction, commitment, and competence to the performance of Teacher of Senior High School in Tebing Tinggi, Meranti region in Riau. The research aims to: (1) analyze the determination of satisfaction, commitment, and competence to the performance of Teacher of Senior High 2 School simultanously (2) analyze the determination of satisfaction, commitment, and competence to the performance of Teacher of Senior High School partially (3) show where is variabel the most determination among satisfaction, commitment, and competence to the performance of Teacher of Senior High School. The research population are 51 Teacher of Senior High School 2 in Tebing Tinggi. The instrument and method of data collection is Likert Scale questionnaire collected from the Teachers. The research applies descriptive data analysis, inreferential test and classical assumption test. The research result shows that there are some positive and significant determination of the variables of satisfaction, commitment and competence simultaneously to the performance of Teacher of Senior High School 2 in Tebing Tinggi, This means that the better the variables, the better the performance of Teacher of Senior High School 2 in Tebing Tinggi,. This is shown from the score of ttest > t table dan F test > F table with a significance score of (p) < 0.05. T shows that competence gives the strongest determination to the performance with a significance rate of (p) < 0,05, thus, the higher the competence, the better the performance of Teacher of Senior High School 2.